Risk Management in Strategic Decision Making: A Case Study of Culinary MSME’s in Surabaya - Irra Chrisyanti Dewi; Fabiola Leoparjo; Otje Herman Wibowo (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This research aims to get a better understanding of how small and medium-sized enterprises (SMEs) in Surabaya's food sector are incorporating risk management into their strategic decision-making processes. Even though they have already had a significant impact on Indonesia's economy, these culinary MSMEs face several financial, operational, and commercial challenges that might hinder their continued success in the future. Thus, a qualitative case study was conducted on five food-related MSMEs situated in Surabaya that had just undergone strategic changes. Based on in-depth interviews and participatory observation, the data was analyzed using theme coding and risk matrices according to ISO 31000 (2018). The analysis found that the two biggest operational risks are supply delays and being too reliant on vendors. Financial risk comes from fluctuations in prices, whereas market risk is characterized by variations in consumer preference. In response to these challenges, MSMEs have turned to digitalization, menu expansion, partnerships with local suppliers, and pre-order systems, among other strategies. Through enhancing corporate resilience, these strategies demonstrate a realistic and systematic application of risk management ideas. To bridge the gap between theory and practice regarding risk management implementation among MSMEs situated in urban regions, the study's results may be used by policymakers and business development programs to construct risk-aware support mechanisms. In the end, it proves that even tiny businesses with little resources can benefit greatly from organized risk analysis when making strategic choices.